Reflexão crítica sobre as atividades desenvolvidas no âmbito das unidades educacionais de Prática Profissional do curso de Medicina da Universidade Federal de São Carlos - Souza, Bruno El Jalis (Universidade Federal de São Carlos, 2013)
The objective is to critically and reflectively describe the activities developed within the educational units of Professional Practice of the Medicine course at the Federal University of São Carlos, which took place in three learning cycles. Throughout the description of each cycle there are relevant analyzes in order to support future discussions about the teaching and learning process of this course, specifically in the context of professional practice.
Critical reflection on the activities developed within the educational units of Professional Practice of the Medicine course at the Federal University of São Carlos.
Keywords: Educação médica; Aprendizagem; Prática profissional; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM